Lower Mitochondrial Energy Production of the Thigh Muscles in Patients With Low‐Normal Ankle‐Brachial Index. Issue 9 (30th August 2017) - AlGhatrif, Majd; Zane, Ariel; Oberdier, Matt; Canepa, Marco; Studenski, Stephanie; Simonsick, Eleanor; Spencer, Richard G.; Fishbein, Kenneth; Reiter, David; Lakatta, Edward G.; McDermott, Mary M.; Ferrucci, Luigi
Abstract : Background: Lower muscle mitochondrial energy production may contribute to impaired walking endurance in patients with peripheral arterial disease. A borderline ankle‐brachial index (ABI) of 0.91 to 1.10 is associated with poorer walking endurance compared with higher ABI. We hypothesized that in the absence of peripheral arterial disease, lower ABI is associated with lower mitochondrial energy production. Methods and Results: We examined 363 men and women participating in the Baltimore Longitudinal Study of Aging with an ABI between 0.90 and 1.40. Muscle mitochondrial energy production was assessed by post‐exercise phosphocreatine recovery rate constant ( k PCr) measured by phosphorus magnetic resonance spectroscopy of the left thigh. A lower post‐exercise phosphocreatine recovery rate constant reflects decreased mitochondria energy production.The mean age of the participants was 71±12 years. A total of 18.4% had diabetes mellitus and 4% were current and 40% were former smokers. Compared with participants with an ABI of 1.11 to 1.40, those with an ABI of 0.90 to 1.10 had significantly lower post‐exercise phosphocreatine recovery rate constant (19.3 versus 20.8 ms −1, P =0.015). This difference remained significant after adjusting for age, sex, race, smoking status, diabetes mellitus, body mass index, and cholesterol levels ( P =0.028). Similarly, post‐exercise phosphocreatine recovery rate constant was linearly associated with ABI as a continuous variable, both in the ABI ranges of 0.90 to 1.40 (standardized coefficient=0.15, P =0.003) and 1.1 to 1.4 (standardized coefficient=0.12, P =0.0405). Conclusions: An ABI of 0.90 to 1.10 is associated with lower mitochondrial energy production compared with an ABI of 1.11 to 1.40. These data demonstrate adverse associations of lower ABI values with impaired mitochondrial activity even within the range of a clinically accepted definition of a normal ABI. Further study is needed to determine whether interventions in persons with ABIs of 0.90 to 1.10 can prevent subsequent functional decline.